Future Marketing, New Wave Marketers - Suryani Musi (Ilmu Komunikasi UIN Alauddin Makassar, 2017)
Sales promotion as a means of communication are becoming increasingly expensive, vertical, one to many, and declining confidence. Promotion of integration, which increasingly requires the manufacturer or brand owner, but balanced with reasonable investments (value). The company began looking for opportunities in the following line is expected to lead to tangible results, but may still be on the verge of adequate investment and relying on rumors of low budget high impact. In an era of New wave promotion activities gradually combined with the media, which is more credible, the media, which are horizontal and many-to-many and created the most effective media is a consumer itself. To win the competition in the communications, no longer uses a large budget, but now how you can win the hearts of the people believed to want to side with us so it will be a messenger of products and services sold. This study aims to assess how big a paradigm shift in marketing that characterized the era of New wave of marketing to improve the quality of product promotion activities.